THEOLOGY OF HOSPITALITY FOR INTRA AND INTER-RELIGIOUS HARMONY: AN INDONESIAN PERSPECTIVE - Frans H. M. Silalahi; Linda A. Ersada; Hengki B. Tompo; David Kristanto (Manna Rafflesia, 2024)
The theme hospitality has become an emerging theme for recent theological explorations. The theme is prominent in the entire Bible and is relevant to the current global issues such as religious pluralism, immigrants, even ecological challenges. This article seeks to show the centrality of divine hospitality in the Bible and how it is clearly reflected in the Pentecost narrative in Acts 2. Furthermore, this article seeks to demonstrate how theology of hospitality could be relevant to fostering intra and inter-religious harmony, especially in the context of Indonesia. The hospitality of the Spirit as shown in Pentecost shapes the body of Christ as a community of hospitality that would use gifts of the spirit not for self-aggrandizement but to serve other. Hospitality is also a theological statement. When Christians are being hospitable towards the religious other, they embody the hospitality of God, and thus participating in the mission of God.